Person-centred care and the work-related health and job satisfaction of health and social care professionals: protocol for a prospective longitudinal cohort study combined with qualitative studies (the PCC@Work project) - Cornelia van Diepen; Qarin Lood; Kristoffer Gustavsson; Malin Axelsson; Monica Bertilsson; Gunnel Hensing; Andreas Fors (BMC, 2024)
Abstract Background The interplay of ethical stress, heavy workloads, and job dissatisfaction poses challenges to both the recruitment and retention of health and social care professionals. Person-centred care, rooted in ethical principles, involves collaborative care, and is expected to improve care and job satisfaction. However, prior research on the impact of person-centred care practices on professionals' work-related health and job satisfaction has yielded mixed results, and most studies emanate from residential care. Understanding how person-centred care practices influence health and social care professionals across different care settings thus requires further exploration through rigorous methodology. The overall aim of PCC@Work is to follow, describe, assess, and explore the impact of person-centred care practices in hospital wards, primary care centres and municipal care on health and social care professionals' work-related health and job satisfaction. Methods PCC@Work is designed as a prospective, longitudinal cohort study combined with qualitative studies. A web-based questionnaire will be distributed on five occasions within two years to health and social care professionals in the three care settings. In addition, focus groups and interviews will be conducted with a selection of health and social care professionals to explore their experiences of work-related health and job satisfaction in relation to person-centred practices. Discussion PCC@Work will highlight some of the knowledge gaps on the impact of person-centred care practices regarding work-related health and job satisfaction of health and social care professionals. The uniqueness of the project lies in the multi-method design, combining a prospective longitudinal cohort study with qualitative studies, and the involvement of various professions and settings. This means we will be able to provide a comprehensive and representative understanding of person-centred care practices as a critical component for effective change in the working conditions of health and social care.